Does Organizational Commitment Affect the Relationship Between Personality and Publication Performance? - Eduard Yohannis Tamaela; Mohamad Amin; Ria Stevany Timisela (Univiversitas Dr. Djar Wattiheluw, 2024)
Publication is a key obligation for lecturers, and while Indonesian lecturers have led ASEAN in publication volume, there was a decline in Scopus-indexed publications in 2022. This decline is attributed to personality factors and organizational commitment. The study, using an explanatory research approach, investigates how personality influences publication performance and the role of organizational commitment. It involves lecturers from L2Dikti Region XII, with data collected through questionnaires, interviews, and observations, analyzed using moderation regression. The results show that traits like openness and conscientiousness enhance publication performance, while organizational commitment does not significantly impact or mediate this relationship. However, the study's small sample size limits its generalizability, suggesting future research should involve larger samples, more institutions, and explore additional factors like intrinsic motivation and institutional support.